Pengembangan Teknologi Marketing Pada Syailendra Muda Berbasis Web - M Syahrifudin; Nurahman Nurahman (KLIK: Kajian Ilmiah Informatika dan Komputer, 2020)
Syailendra Muda is a company engaged in the largest, most comprehensive and cheapest printing and service sector, which is located at Jl.A.Yani No 11 Sampit, Central Kalimantan Province, Indonesia. The problem that exists with Syailendra Muda, namely offline marketing arises because the company's insufficient reach is not well known, customers have to come to the store to place an order, and making reports at Syailendra Muda is still manual, resulting in reports that can be crossed out and untidy. The existence of this problem requires sales applications and online reports to input report data via computers or cellphones, so that potential customers do not have to come to the company to place orders and payments can be made through online sales applications, and report making is no longer using handwritten, bothering to write which is a lot in the diary. One of the steps taken was to create a web-based marketing technology development application for Syailendra Muda. To create a web-based information system, we need a Macromedia Dreamweaver CS4 programming language editor, PHP programming language, and MySQL database